KEWENANGAN FATWA MAJELIS ULAMA INDONESIA TERHADAP LABEL KOSMETIK DI INDONESIA - Mega Ayu Ningtyas; Safarudin Harefa (PERADA, 2022)
Issued by the director of POM RI (director of pharmaceutical development and food supervision of the republic of indonesia) require food producers to attach additional labels with information on food ingredients, the authority of mui to handle the process of monitoring the circulation of products labeled as halal, mui plays an important role in increasing consumer confidence who enjoys cosmetics. Halal and produce legal certainty and benefits. From manufacturing to product release, we need a competent body to determine which products are on the market. In this case, mui on behalf of indonesian muslims plays a very important and much needed role in determining which products entering the indonesian market are halal products. In addition, the government's role in assessing and monitoring the performance of the mui in deciding halal-labeled products is very important. In this case, the existence of halal-labeled cosmetics really requires significant intervention from the authorities to determine it. Otherwise, society itself is the victim, and when people are victimized, it has an effect. It is not easy to even paralyze the indonesian cosmetic market. Therefore, the function and authority of the mui as a representative in general is very important for all indonesian people, especially on behalf of the voice of muslims